Fear of Appreciation - Levy Yeyati, Eduardo, 1965- 1965- (The World Bank, 2007)
In recent years the term "fear of floating" has been used to describe exchange rate regimes that, while officially flexible, in practice intervene heavily to avoid sudden or large depreciations. However, the data reveals that in most cases (and increasingly so in the 2000s) intervention has been aimed at limiting appreciations rather than depreciations, often motivated by the neo-mercantilist view of a depreciated real exchange rate as protection for domestic industries. As a first step to address the broader question of whether this view delivers on its promise, the authors examine whether this "fear of appreciation" has a positive impact on growth performance in developing economies. The authors show that depreciated exchange rates appear to induce higher growth, but that the effect, rather than through import substitution or export booms as argued by the mercantilist view, works largely through the deepening of domestic savings and capital accumulation